Overparenting and Homework: The Student's Task, But Everyone's Responsibility - Locke, Judith Y.; Kavanagh, David J.; Campbell, Marilyn A. (Journal of Psychologists and Counsellors in Schools, 2016)
A high level of parental involvement is widely considered to be essential for optimal child and adolescent development and wellbeing, including academic success. However, recent consideration has been given to the idea that extremely high levels of parental involvement (often called ‘overparenting’ or ‘helicopter parenting’) might not be beneficial. This study used a newly created overparenting measure, the Locke Parenting Scale (LPS), to investigate the association of overparenting and children's homework. Eight hundred and sixty-six parents completed online questionnaires about their parenting beliefs and intentions, and their attitudes associated with their child's homework. Parents with higher LPS scores tended to take more personal responsibility for the completion of their child's homework than did other parents, and ascribed greater responsibility for homework completion to their child's teacher. However, increased perceived responsibility by parents and teachers was not accompanied by a commensurate reduction in what they perceived was the child's responsibility. Future research should examine whether extreme parental attitudes and reported behaviours translate to validated changes in actual homework support.